UPAYA MENINGKATKAN PEMBELAJARAN SERVIS BAWAH PERMAINAN BOLA VOLI MINI MELALUI MEMODIFIKASI PADA SISWA SISWI KELAS 5 SD NEGERI 48 KOTA LUBUKLINGGAU - Rais Firlando; Muhammad Supriyadi; Muhammad Suhdy (LP4MK STKIP PGRI Lubuklinggau, 2021)
The aim of this research is to improve the learning of serving under the game of mini volleyball through modifications at SD Negeri 48 Lubuklinggau City, Ilir Timur II District, Palembang City. The method used in this study was Classroom Action Research (CAR), which consisted of 2 cycles and each cycle consisted of one meeting or 2 x 40 minutes which included the following activities, namely planning, implementing, observing or observing and reflecting. The subjects of this study were fifth grade students at SD Negeri 48 Lubuklinggau City, second semester of the 2022/2023 academic year. The results of this study are as follows: The average score of the volleyball underhand technique in the initial KKM test increased to 38%. The average score of the under serve technique in the KKM cycle 1 increased to 59%. The average score of the under serve technique in the 2nd KKM cycle increased to 79%. The average score of students' attitudes towards the learning process in cycle 1 of the KKM reached 60%. The average score in the 2nd cycle of KKM learning increased to 85%. From the test results above, it can be concluded that learning to serve in volleyball can be improved.